Pleuroperitoneal Leak: An Unusual Cause of Acute Shortness of Breath in a Peritoneal Dialysis Patient - D. P. Ramaema; P. Mpikashe (Case Reports in Radiology, 2014)
Introduction. Pleuroperitoneal leak is an uncommon complication of continuous ambulatory peritoneal dialysis (CAPD), with an estimated incidence of 1.6%. It should be suspected in these patients when they present with recurrent unilateral pleural effusions and/or acute shortness of breath following dialysate infusion. Case Presentation. We present the case of a 25-year-old female patient who had acute hydrothorax as a result of pleuroperitoneal leak complicating continuous ambulatory peritoneal dialysis (CAPD), which was confirmed on peritoneal scintigraphy. Conclusion. Continuous ambulatory peritoneal dialysis patients presenting with acute shortness of breath and/or recurrent unilateral pleural effusion should be investigated with peritoneal scintigraphy to exclude pleuroperitoneal leak.